Identification & Examination of Critical Success Factor for Projects: A Case Study of Tamil Nadu Geographical Information System (TNGIS). Issue 2 (December 2019) - Meshram, Sunil; Ahmed, Salma
Information and communication technology (ICT) usage in governance has become an indispensable element to ensure quality of service provided by the government. The intensity of ICT usages and its impact on quality of service have revealed that effective utilization of the e-governance and its proximity needs periodical introspection in order to enrich the quality of the service. Especially, the significance of government-to-government (G2G) operations depends on the intensity of usage and the inclination of the personnel towards utilization. The present study examines the intensity of the components which influence the success of the Tamil Nadu Geographical Information System (TNGIS) project through information system (IS) model. The study collected information from TNGIS users. The study utilized structural equation modelling to validate the IS model. The results indicated that information quality, system quality, service quality, perceived usefulness, perceived ease of use, and perceived satisfaction of TNGIS have enhanced the quality of service and satisfaction of the personnel utilizing the services. Further, there is a strong need to enhance the infrastructure of ICTs to enrich the quality of service.